USING RUBRICS TO FOSTER ESP ADVANCED LEARNERS WRITING SKILLS DEVELOPMENT IN ‘’LYCEE TECHNIQUE ET PROFESSIONNEL DE PORTO NOVO’’ (LTP-PN). - TEBA, Corneille Sourou (My University, 2024)
This study examines the impact of rubrics on the enhancement of writing skills among advanced learners of English for Specific Purposes (ESP) in Benin. A mixedmethod approach, encompassing both quantitative and qualitative data collection, was utilized. Data were gathered through questionnaires distributed to five teachers and fifty students, five classroom observations, and an analysis of forty students’ writing performances in both analytical (rubrics-based) and holistic evaluation settings. Descriptive statistics were used to analyze the data, with correlation and significance tests conducted. The findings indicated that the primary obstacles to developing writing skills in ESP classes are inappropriate assessment methods, particularly the holistic model and the ineffective teaching strategies. The study also reveals a significant improvement in students’ writing performance within an analytical evaluation setting. The paper proposes context-specific teaching, learning, and evaluation activities, along with rubrics, to address grading challenges.
Keywords: Keywords: Rubrics; Writing Skills Development; English for Specific Purposes; (ESP); Holistic evaluation.